PERBANDINGAN PEMBERITAAN SEPUTAR KEBIJAKAN TAX AMNESTY DI MEDIA ONLINE KOMPAS.COM DENGAN VIVA.CO.ID (Studi Perbandingan Dengan Menggunakan Analisis Framing Model Pan dan Kosicki Pada Media Online) - Siswanta, Ary Sepriyanto, Buddy Riyanto & (Transformasi, 2017)
This research aimed to describe the comparison news frame on Amnesty Tax policy inthe first period with Viva.co.id and Kompas.com online media model Zhondang Pan and GeraldM. Kosicki. This study aimed to describe the comparison frame pemberitaaan Amnesty Taxpolicy in the first period with Viva.co.id and Kompas.com online media model Zhondang Panand Gerald M. Kosick. This type of research used in this research is descriptive qualitative.Data collection technique used REMEDY stage, the stage of data analysis, and interpretationphase. And data analysis techniques. The results showed framing Kompas.com against taxamnesty tax amnesty is seen as an effort to help grow the economy of Indonesia, while framingViva.co.id looking at tax amnesty as an alternative effort to help the Indonesian economy but thepolicy has many shortcomings that need a lot of socialization and revision.Key words: framing analysis, tax amnesty, Kompas.com and Viva.co.id